The Ebro river basin - Barcelo, Damia; Petrovic, Mira (The handbook of environmental chemistry, 2011)
The Ebro is a typical Mediterranean river characterized by seasonal low flows and extreme flush effects, with important agricultural and industrial activity that has caused heavy contamination problems. This volume deals with soil-sediment-groundwater related issues in the Ebro river basin and summarizes the results generated within the European Union-funded project AquaTerra. The following topics are highlighted: Hydrology and sediment transport and their alterations due to climate change, aquatic and riparian biodiversity in the Ebro watershed, occurrence and distribution of a wide range of priority and emerging contaminants, effects of chemical pollution on biota and integration of climate change scenarios with several aspects of the Ebroâ??s hydrology and potential impacts of climate change on pollution. The primary objective of the book is to lay the foundation for a better understanding of the behavior of environmental pollutants and their fluxes with respect to climate and land use changes